Formulasi dan Karakteristik Bihun Tinggi Protein dan Kalsium dengan Penambahan Tepung Tulang Ikan Patin (Pangasius Hypopthalmus) Untuk Balita Stunting - Nur Afrinis; Verawati Besti; Harahap Dewi Anggraini (Media Kesehatan Masyarakat Indonesia, 2018)
Stunting is the nutritional problems in Indonesia. The direct cause of stunting was infectious disease andinadequate food intake such as protein and calcium deficiency. Patin fishbone powder contain high in protein, calciumand phosphor needed for growth children under five years. Utilization of patin fishbone powder is processedinto flour and made rice noodle for children under five years stunting. The aims of the research were to determinethe best formula and characteristics of rice noodles high protein and calcium with addition of patin fishbone powder(Pangasius hypopthalmus) for children under five years stunting. A complete randomized design was used forthe experiment. Variables analyzed were : chemical properties (water content, total fat, total protein, carbohydrateby difference and ash content), calcium and phosphor, and sensory properties (hedonic test and hedonic quality).Hedonic test was conducted to determine the level of consumer acceptance of 25 semi-trained panelists. Data wereanalyzed by ANOVA. The results showed rice n noodles with addition of patin fishbone powder (HypopthalmusPangasius) water content 6.79%, ash 64.23%, protein content 20.39%, fat content 3.36%, carbohydrate 8.35%,calsium 1002.00 mg/100g and fosfor 12.80 mg/100g. Based on ANOVA test there is the effect of addition of patinfishbone flour to taste (p=0,001) and smell (p=0,041) , while color (p=0.116) and texture (p=0,102) have no effect.The best formula was rice noodles from F1 (4%) for children under five years stunting.